Formulation and Production of Pegagan (Centella asiatica) Extract Liposomes as an Alzeheimer Preventive Agent - Faridha Yenny (Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction: Liposomes containing standardized Centella asiatica extract (CAE) were developed to enhance the solubility of its phytoconstituents for oral administration with the aim of treating Alzheimer’s disease. Materials and Methods: CAE was obtained using the Soxhlet extraction method. The formulation was optimized using Design-Expert software, and solvent evaporation and ionotropic gelation methods were adopted to prepare CAE liposomes (CAEL) and chitosan-coated CAE liposomes (CCAEL). The prepared CCAEL was characterized in terms of vesicle size, entrapment efficiency, polydispersity index, drug content analysis, Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), transmission electron microscopy (TEM), atomic force microscopy (AFM), in vitro drug release, in vitro antioxidant activity, ex vivo permeation studies, and stability studies. Results and Discussion: Proper incorporation of the drug into the chitosan–phospholipid complex was confirmed by FTIR and DSC analyses. The surface morphology of the prepared formulation was examined using TEM and AFM. In vitro drug release studies showed that CAE exhibited a lower release rate of 35.34 ± 0.30% over approximately 10 hours due to poor solubility, whereas about 58.6 ± 0.42% drug release was observed from the optimized CCAEL. In vitro antioxidant studies demonstrated that the free radical scavenging activity of CAE was retained even after complexation with phospholipids, with 2,2-diphenyl-1-picrylhydrazyl (DPPH) inhibition of 73.84% at 50 μg/mL compared to 74.4% for free CAE. In vitro intestinal studies confirmed an increased permeation rate due to encapsulation within the chitosan–phospholipid complex. Stability studies indicated that chitosan-coated liposomes were stable owing to the compact chitosan coating layer. Conclusion: The results of this study are encouraging, demonstrating improved solubility and permeability. Further detailed preclinical studies are required to ensure optimal product development.